If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 9)(x + -3) = (x + 1) Reorder the terms: (9 + x)(x + -3) = (x + 1) Reorder the terms: (9 + x)(-3 + x) = (x + 1) Multiply (9 + x) * (-3 + x) (9(-3 + x) + x(-3 + x)) = (x + 1) ((-3 * 9 + x * 9) + x(-3 + x)) = (x + 1) ((-27 + 9x) + x(-3 + x)) = (x + 1) (-27 + 9x + (-3 * x + x * x)) = (x + 1) (-27 + 9x + (-3x + x2)) = (x + 1) Combine like terms: 9x + -3x = 6x (-27 + 6x + x2) = (x + 1) Reorder the terms: -27 + 6x + x2 = (1 + x) Remove parenthesis around (1 + x) -27 + 6x + x2 = 1 + x Solving -27 + 6x + x2 = 1 + x Solving for variable 'x'. Reorder the terms: -27 + -1 + 6x + -1x + x2 = 1 + x + -1 + -1x Combine like terms: -27 + -1 = -28 -28 + 6x + -1x + x2 = 1 + x + -1 + -1x Combine like terms: 6x + -1x = 5x -28 + 5x + x2 = 1 + x + -1 + -1x Reorder the terms: -28 + 5x + x2 = 1 + -1 + x + -1x Combine like terms: 1 + -1 = 0 -28 + 5x + x2 = 0 + x + -1x -28 + 5x + x2 = x + -1x Combine like terms: x + -1x = 0 -28 + 5x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '28' to each side of the equation. -28 + 5x + 28 + x2 = 0 + 28 Reorder the terms: -28 + 28 + 5x + x2 = 0 + 28 Combine like terms: -28 + 28 = 0 0 + 5x + x2 = 0 + 28 5x + x2 = 0 + 28 Combine like terms: 0 + 28 = 28 5x + x2 = 28 The x term is 5x. Take half its coefficient (2.5). Square it (6.25) and add it to both sides. Add '6.25' to each side of the equation. 5x + 6.25 + x2 = 28 + 6.25 Reorder the terms: 6.25 + 5x + x2 = 28 + 6.25 Combine like terms: 28 + 6.25 = 34.25 6.25 + 5x + x2 = 34.25 Factor a perfect square on the left side: (x + 2.5)(x + 2.5) = 34.25 Calculate the square root of the right side: 5.852349955 Break this problem into two subproblems by setting (x + 2.5) equal to 5.852349955 and -5.852349955.Subproblem 1
x + 2.5 = 5.852349955 Simplifying x + 2.5 = 5.852349955 Reorder the terms: 2.5 + x = 5.852349955 Solving 2.5 + x = 5.852349955 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.5' to each side of the equation. 2.5 + -2.5 + x = 5.852349955 + -2.5 Combine like terms: 2.5 + -2.5 = 0.0 0.0 + x = 5.852349955 + -2.5 x = 5.852349955 + -2.5 Combine like terms: 5.852349955 + -2.5 = 3.352349955 x = 3.352349955 Simplifying x = 3.352349955Subproblem 2
x + 2.5 = -5.852349955 Simplifying x + 2.5 = -5.852349955 Reorder the terms: 2.5 + x = -5.852349955 Solving 2.5 + x = -5.852349955 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.5' to each side of the equation. 2.5 + -2.5 + x = -5.852349955 + -2.5 Combine like terms: 2.5 + -2.5 = 0.0 0.0 + x = -5.852349955 + -2.5 x = -5.852349955 + -2.5 Combine like terms: -5.852349955 + -2.5 = -8.352349955 x = -8.352349955 Simplifying x = -8.352349955Solution
The solution to the problem is based on the solutions from the subproblems. x = {3.352349955, -8.352349955}
| 8(-8+5b)+6=222 | | 5+5p=-30 | | 5n-(9-5n)=9 | | 2(x+3)=8(x-1) | | 21q+73=62q-51+8q | | B=(d/1-r) | | 8n+21n=-3 | | (25/8)(24/5) | | 3x-(x+1)=7 | | X+5+x+14=15 | | 3x+2y-5=ax+by+1 | | -144=-3-3(5+6k) | | 84x^2-238x-196=0 | | 7n+12=32 | | (25/8)(2/5) | | 24-x/3=6 | | 5(3x-5)=6(x-2)-19 | | (4n/7)+(3n/2)=-3 | | (12n+20)-4-8n=6-2n | | 3x^2+40x+112=0 | | 3/4x-1/4x=-11 | | 25/8*2/5 | | -13+5x=12 | | 1/(14-3x)=2/(5x+4) | | 0.7t=0.3+0.9t | | 2p+5r=a | | 3(5-2r)-2(-3r+1)= | | 10x-(4x-8)=50 | | 4(5-4k)=-60 | | 8-34= | | 4+6/x | | 14=5x+2 |